LEVELS OF NEUROSPECIFIC ENOLASE AND ENOLASE-SPECIFIC AUTOANTIBODIES IN BLOOD SERUM OF THE PATIENTS WITH AUTOIMMUNE THYROPATIES - N. N. Tsybikov; A. A. Zueva; E. B. Zhigzhitova; E. V. Prutkina (Медицинская иммунология, 2014)
The patients with autoimmune thyroiditis and various functional states of thyroid gland, and diffuse toxic goiter with pronounced thyrotoxicosis were studied for neurospecific enolase and enolase-specific autoantibodies levels in blood serum. Increased concentrations of neurospecific enolase and specific autoantibodies were revealed in all groups of the patients. A conclusion was drawn that nervous system may be involved into pathological process during development of thyropaties.